Social capital : an international research program - Lin, Nan, 1938-; Erickson, Bonnie H. (Oxford : Oxford University Press, 2008)
The volume brings together some of the leading scholars around the world working on social capital to study how individuals and groups access and use their social relations and social connections to do better in society in order to achieve their goals.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social capital (Sociology); Community development; Community organization; Social participation